1994
DOI: 10.1099/13500872-140-2-369
|View full text |Cite
|
Sign up to set email alerts
|

Stability and function of the signal peptide of the pCloDF13-derived bacteriocin release protein

Abstract: The pCloDFl3-derived bacteriocin release protein (BRP) is synthesized as a prelipoprotein with a signal peptide which remains stable after processing. This signal peptide accumulates in the cytoplasmic membrane and is, together with the mature BRP, required for efficient release of cloacin DF13. We investigated the structural requirements for stability of the BRP signal peptide by constructing hybrid signal peptides consisting of parts of the BRP and Lpp signal peptides. Signal peptide stability was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…E. coli W3110 and W3110 degP were used as the hosts for the induction experiments, while HB101 was used as the host for all recombinant constructions. Cultures used for [ 35 S]methionine labeling experiments were grown at 37°C in M9 medium supplemented with 0.5% methionine assay medium, 4 mg of glycerol per ml, 10 g of thiamine per ml, and 50 g of ampicillin per ml, while those labeled with [ 3 H]glycerol were grown in the same medium supplemented with 4 mg of sodium lactate per ml rather than glycerol as the carbon source. For quasilysis and colicin secretion assays, cultures were grown in Luria-Bertani medium (24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. coli W3110 and W3110 degP were used as the hosts for the induction experiments, while HB101 was used as the host for all recombinant constructions. Cultures used for [ 35 S]methionine labeling experiments were grown at 37°C in M9 medium supplemented with 0.5% methionine assay medium, 4 mg of glycerol per ml, 10 g of thiamine per ml, and 50 g of ampicillin per ml, while those labeled with [ 3 H]glycerol were grown in the same medium supplemented with 4 mg of sodium lactate per ml rather than glycerol as the carbon source. For quasilysis and colicin secretion assays, cultures were grown in Luria-Bertani medium (24).…”
Section: Methodsmentioning
confidence: 99%
“…In studies of the processing and degradation of the cloacin DF13 lysis protein signal peptide, a lysis protein synthesized with the unstable signal peptide of Braun's lipoprotein did not function in cloacin release but did cause lethality and quasilysis (23). Expression of the stable signal peptide alone caused lethality and quasilysis but no cloacin release, as did a number of hybrid lysis protein-major lipoprotein signal peptides of varying stability (33,35). In addition, when the stable signal peptide and the inactive lysis protein synthesized with an unstable signal peptide were expressed together, a small amount of cloacin DF13 was released from the cells (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the colicin E1 BRP signal peptide is of intermediate stability, analogous to a hybrid signal peptide consisting of the 10 amino-terminal residues of the Lpp signal peptide and the 10 carboxyl-terminal residues of the pCloDFI3 BRP signal peptide. This hybrid signal peptide (10Lppl0BRP) functions in the release of cloacin DF13, albeit with reduced efficiency [118]. Similar to the colicin E1 BRP signal peptide, this hybrid signal peptide does not accumulate upon processing of the BRP precursor.…”
Section: Brp Signal Peptidesmentioning
confidence: 99%
“…Stability appears to be an intrinsic property of most BRP signal peptides, since the colicin E2-and pCIoDF13 BRP signal peptides can be visualized on a gel after radiolabelling, when they are expressed as separate entities [111,114]. By constructing hybrid signal peptides consisting of a part of the unstable Lpp signal peptide and a part of the stable pCIoDFI3 BRP signal peptide, it was shown that the amino-terminal segment of the BRP signal peptide together with the carboxyl-terminal alanine residue are important for stability [118].…”
Section: Brp Signal Peptidesmentioning
confidence: 99%